2009
DOI: 10.1088/0022-3727/42/18/182004
|View full text |Cite
|
Sign up to set email alerts
|

Small surface wave discharge at atmospheric pressure

Abstract: A small surface wave driven source produces plasma at atmospheric pressure. Microwave power at frequency 2.45 GHz is coupled with the source and a discharge is ignited at power levels below 10 W. The coaxial exciter of the surface waves has a length of 10 mm because its dielectric is a high permittivity discharge tube. The plasma source operates as a plasma jet in the case of plasma columns longer than the tube length. The source maintains stable plasma columns over a wide range of neutral gas flow and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…It can be seen that the plasma length is strongly dependent on the microwave absorbed power. This behavior is also observed in a surface wave discharges generated by the pulse and CW modes [26]- [28]. It should be noted that tube dimension, wall material, and frequency can also affect the sustained surface wave plasma column length [27].…”
Section: Resultssupporting
confidence: 52%
“…It can be seen that the plasma length is strongly dependent on the microwave absorbed power. This behavior is also observed in a surface wave discharges generated by the pulse and CW modes [26]- [28]. It should be noted that tube dimension, wall material, and frequency can also affect the sustained surface wave plasma column length [27].…”
Section: Resultssupporting
confidence: 52%
“…The emission spectra of the Ar plasma jet alone confirmed that the major domination of spectral lines was obtained due to excited Ar species, whereas no spectral lines were emerging from Ar + ions. The emission spectra of the Ar plasma jet during the in situ degradation of isothiazolin‐3‐one at 27 kV showed various new peaks due to nitrogen second positive system (NSP) (336.3, 355.6, and 377.5 nm) and hydrogen species (H α = 655.8, H β = 489.6, and H γ = 432.3 nm) (hydrogen atom in the Balmer series) (Attri et al, 2015; Kissovski et al, 2009; National Institute of Standard and Technology (NIST Database), 2013; Onyshchenko et al, 2015; Rezaei et al, 2018). The identification of NSP during in situ processes may be ascribed to the breaking of isothiazolin‐3‐one molecules in aqueous and was excited via sharing energy by plasma species or by excitation of N 2 molecules in diffused ambient air at plasma jet–liquid interface.…”
Section: Resultsmentioning
confidence: 99%
“…[9] For the simultaneous modelling of the energy supply system, the plasma processes in the plasma source and the gas flow, it is appropriate to use the COMSOL software package. [10][11][12] F I G U R E 1 Schematic of electrothermal microwave plasma thruster The electric propulsion technologies for satellites are gaining popularity and are becoming the preferred choice over chemical thrusters. The main reason is that the chemical thrusters use the energy stored in the propellant, which is limited to the energy of the molecular bonds in it, while the electrothermal thrusters use the available onboard electrical energy to accelerate the propellant.…”
Section: Introductionmentioning
confidence: 99%